Dimensions of culture in relation to teamwork for South Africans living abroad - Singh, Ashika (My University, 2011)
South Africa has experienced changing times. It is a country that has undergone many political changes that involved various ethnic groups. Managing diversity brings benefits but requires skills and training. Organisations therefore need to manage diversity effectively. Organisations need to understand culture in order to mould it into a high performance culture. Teamwork exists in various areas such as the sporting world and the corporate world, and there are many challenges that teams need to overcome in order to perform optimally. Organisations need to address virtual and geographical team issues and support these teams. Companies must select the correct expatriates and support them according to their individual needs. The aim of this study was to test the findings of the study conducted by Weimer (2006) with the added dimension of investigating the self-identified diversity characteristic of South Africans living both locally and abroad, in relation to the teamwork profiles described by Hofstede (2001). The questionnaires as used by the Weimer (2006) study were distributed to respondents based in three countries namely South Africa, United Kingdom and the Middle East (Qatar and Dubai). Seventy-five completed questionnaires were returned. The profile obtained by Weimer (2006) noted that South African ethnic groups have a distinct profile with no major variations between groups, transcending race, religion and ethnicity. This study confirmed the results obtained by Weimer (2006). It was found that employees‟ values held with regard to teamwork, do not differ based on the country where they are located.
MBA - WBS
Keywords: Teamwork; Culture; Diversity management